2008
DOI: 10.1111/j.1740-8709.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Newborn care practices in Pemba Island (Tanzania) and their implications for newborn health and survival

Abstract: Newborn mortality accounts for about one-third of deaths in children under five. Neglecting this problem may undermine the fourth Millennium Development Goal of reducing child mortality by two-thirds by 2015. This study was conducted in Tanzania, where an estimated 32/1000 infants die within the first 28 days. Our objective was to describe newborn care practices and their potential impact on newborn health. We interviewed two purposive samples of mothers from Pemba Island, a predominantly Muslim community of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 19 publications
5
35
1
Order By: Relevance
“…It is likely that the use-rate of a clean thread could be substantially increased, using the same channels that have promoted new blade-use which is extremely high (96%) (10). The high use-rate of a new blade has been reported in other African settings (12,14). However, studies from Ghana and Uganda (11,13) found that the use-rate of a clean thread to tie the cord was also high.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is likely that the use-rate of a clean thread could be substantially increased, using the same channels that have promoted new blade-use which is extremely high (96%) (10). The high use-rate of a new blade has been reported in other African settings (12,14). However, studies from Ghana and Uganda (11,13) found that the use-rate of a clean thread to tie the cord was also high.…”
Section: Discussionmentioning
confidence: 68%
“…Knowledge does not appear to be essential for practice because despite low knowledge, delivering on a clean cloth was the norm as reported in the narratives; quantitative data from the study area show that women frequently prepared for delivery by purchasing soap, preparing a clean cloth for drying the child, and cleaning the floor (10). The use of a new or washed cloth was also found to be common in Ghana, Uganda, and Pemba Island (11,12,13,14). This suggests that messages about preparing and delivering on a clean surface do not always need to be a focus of newborn care interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This survey adds to a small but growing literature on newborn care practices at community level in Sub-Saharan Africa [18,28-32]. In the population served by the health facilities included in this study, the majority of women made one antenatal care visit to a health facility, but less than half made four or more visits.…”
Section: Discussionmentioning
confidence: 99%
“…35 In a study from Tanzania, the practice of bathing newborns immediately after delivery was shown to be motivated by concerns about 'ritual pollution'. 36 In Ghana, early bathing was linked to reducing body odor in later life, shaping the baby's head, and helping the baby sleep and feel clean, and informants felt that changing bathing behaviors would be difficult, especially as babies are bathed early in facilities. 37 A study from Dhaka, Bangladesh, explained that babies are typically bathed soon after birth to purify them from the birth process.…”
Section: Management Of Newborn Hypothermiamentioning
confidence: 99%